Biochemotherapy of mestastic melanoma – clinical experience and perspective analysis - Żołnierek, Jakub; Paprocka-Langiewicz, Joanna; Leśniewski-Kmak, Krzysztof; Langiewicz, Przemysław; Sarosiek, Tomasz; Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2003)
Metastatic cutaneous melanoma as a chemoresistant neoplasm is a great challenge to the contemporary oncology. In this article we analyze recent results of melanoma treatment with combined chemotherapy and cytokines (biochemotherapy) on basis of both own experience and medical literature. We try to estimate the real indications for biochemotherapy in the treatment of metastatic melanomas and show some of new points of diagnostics and practical use. Between December 1996 and March 2003 in the Oncology Department of the Central Clinical Hospital of the Military Medical Institute 39 patients with metastatic melanomas received CVD chemotherapy (dacarbazine 800 mg/m2 d. 1, cisplatin 20 mg/m2 d. 1–4 and vinblastine 1.6 mg/m2 d. 4 and 5) intravenously combined with interleukin-2 (9 mlnU/m2 d. 1–4) and interferon alpha (5 mlnU/m2 d. 1–5) administered subcutaneously (BIO). We planned sequential treatment schedule of three cycles of CVD (d. 1–5, 22–26, 43–47) and three cycles of BIO (d. 6–10, 17–21, 27–31). Median age was 44 (22–62). Before biochemotherapy ten patients (26%) had metastasectomy (NED before treatment), twenty (51%) had metastases only in lymph nodes, soft tissue and lungs. Toxicities were recorded according WHO criteria for all patients receiving at least one cycle of CVD chemotherapy and one immunotherapy (BIO), that is 39 (100%), responses were recorded for 25 patients (64%) with measurable disease, and time to progression (TTP), progression free survival (PFS) and overall survival (OS) for 34 patients (87%). Non-hematological grade 3 or 4 toxicity was moderate: fever – 7 pts (17.7%), nausea and vomiting – 3 pts (7.7%), anorexia – 3 pts (7.7%), flu-like syndrome – 3 pts (7.7%). Grade 3 or 4 neutropenia was confirmed in 9 pts (23.1%), thrombocytopenia in 5 pts (12.8%) and anemia in 3 pts (7.7%). We obtained 6 CR (24%) and 8 PR (32%). Median TTP (month) was 6.5 (2–49), PFS of 7 (2–49) and OS of 11.5 (5–64).